Covid-19, workplace challenges / Azian Abd Ghani, Zainuddin Zakaria and Siti Najihah Amir Hamzah - Abd Ghani, Azian; Zakaria, Zainuddin; Amir Hamzah, Siti Najihah (Universiti Teknologi MARA, Perlis, 2021)
This paper is written to enlighten how organizations monitor employees' work performance from home versus working in the office as a result of the Covid-19 pandemic. The objective of this article was to determine how organizations were able to measure the performance of their employees when they were working from home. Secondly, to evaluate how organizations were able to monitor virtual workload as versus traditional workload. Finally, through scrutinizing the new workplace normal articles, the author derived the third objective which was to determine how the employees balanced their work and family disputes during the Covid-19 pandemic. Several related articles were scrutinized to demonstrate the current workplace scenario as opposed to the traditional practices. At the end of the article, we proposed several monitoring measures and how employees’ performance can be improved during the Covid-19 pandemic. Flexibility in goal setting, teamwork and regular performance feedback will psychologically lead to positivity in work performance. Whilst, social support, job autonomy, workload and monitoring would reduce employees’ procrastination in carrying out their virtual workload. Lastly, a 360° social support, flexible schedule, mental therapy and boundary management create conductivity working at home and being able to overcome work and mental stress thus create a healthy working environment.